Surgical-allogeneic facial reconstruction: facial transplants - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Bannwart, Lisiane Cristina [UNESP]; Haddad, Marcela Filié [UNESP]; Pereira, Leonardo Viana [UNESP]; Filho, Aljomar José Vechiato [UNESP] (My University, 2014)
Several factors including cancer, malformations and traumas may cause large facial mutilation. These functional and aesthetic deformities negatively affect the psychological perspectives and quality of life of the mutilated patient. Conventional treatments are prone to fail aesthetically and functionally. The recent introduction of the composite tissue allotransplantation (CTA), which uses transplanted facial tissues of healthy donors to recover the damaged or non-existent facial tissue of mutilated patients, resulted in greater clinical results. Therefore, the present study aims to conduct a literature review on the relevance and effectiveness of facial transplants in mutilated subjects. It was observed that the facial transplants recovered both the aesthetics and function of these patients and consequently improved their quality of life.
Keywords: Composite tissue allotransplantation; Facial transplantation; Microsurgery; Rehabilitation